Effect of Curing Modes on Depth-of-Cure in Bulk-Fill Composite - Zainab Haji; Robia Ghafoor (Elsevier, 2021)
Aim or Purpose: LED unit has different curing modes with variable intensities that influence polymerization of composite restorative material. Bulk-Fill composites claim more depth of cure compared to conventional composites. However, they have conflicting reports on their success. Hence, the purpose of this study is to explore the curing mode that could result in maximum depth cure in Bulk Fill restorative material. Materials and Methods: Thirty-three cylindrical composite specimens with dimension of 8mm length and 4mm diameter were made in preformed Teflon mold/frame by polymerization with LED using one of the three modes: Group1 constant mode; Group 2 pulse and Group 3 ramped mode. Once polymerized, each specimen was extruded from the mould and using the ISO 4049 scrapping method, uncured resin was removed. Specimen lengths were measured with a Vernier calliper. Each specimen was measured thrice and the mean was taken for the depth-of-cure. The data was subjected to ANOVA and Tukey's post hoc analysis. Results: The pulse, constant and ramped modes resulted in depth of cure of SDR BulkFill composite of 2.88 ± 0.27mm, 2.92 ± 0.29mm and 3.18 ± 0.26mm, respectively. The difference in depth of cure between pulse and ramped curing mode was statistically significant on post-hoc analysis (p-value=0.04). Conclusion: Maximum depth of cure of SDR BulkFill composite was achieved by ramped cure mode of LED unit followed by Constant and Pulse modes.